Effects of a competency‐based professional development training on children's physical activity and staff physical activity promotion in summer day camps. Issue 143 (September 2014) - Weaver, R. Glenn; Beets, Michael W.; Turner‐McGrievy, Gabrielle; Webster, Collin A.; Moore, Justin
Abstract : The YMCA of the USA serves more than nine million youth in its summer day camping programs nationwide. In spring 2011, the YMCA of Columbia, SC, with support from the University of South Carolina, adopted a competency‐based staff‐level training approach in an attempt to align staff behaviors with the YMCA of the USA new physical activity standards for summer camp programs. This chapter presents findings from a multiyear evaluation of a competency‐based training approach using a single group design with preassessments and multiple postassessments. Training consisted of participatory exercises and video demonstrations. Data on staff physical activity promotion behaviors were collected using SOSPAN, an instrument that utilizes momentary time sampling to record instances of staff physical activity promotion behaviors consistent with physical activity standards. This chapter describes how a competency‐based professional development training may be effective at increasing physical activity promoting and decreasing physical activity discouraging staff behaviors and related child activity levels.